Protease and Reverse Transcriptase Mutation Patterns in HIV Type 1 Isolates from Heavily Treated Persons: Comparison of Isolates from Northern California with Isolates from Other Regions - GONZALES, MATTHEW J. (2003)
We compared HIV-1 subtype B reverse transcriptase (RT) and protease mutation patterns in isolates from heavily treated persons in Northern California with those from persons described in the published literature predominantly from other parts of the United States and Europe. There were few differences in the prevalence of single, double, and triple mutations between the two sets of sequences. More complex patterns of mutations could be characterized by clustering the sequences into eight groups of RT sequences and nine groups of protease sequences according to the presence of known drug-resistance mutations. This clustering accounted for 63% of the variation at RT inhibitor-resistance positions and 68% of the variation at protease inhibitor-resistance positions. The majority of clusters contained Northern California and literature sequences in similar proportions.